Generalized self-adaptive algorithm for solving split common fixed point problem and its application to image restoration problem. Issue 7 (2nd July 2020) - Suparatulatorn, Raweerote; Khemphet, Anchalee; Charoensawan, Phakdi; Suantai, Suthep; Phudolsitthiphat, Narawadee
ABSTRACT: In this work, we introduce a self-adaptive algorithm, based on viscosity approximation methods, to solve split common fixed point problems of demicontractive operators in real Hilbert spaces. Besides, the strong convergence theorem for the algorithm is established under some additional assumptions. On top of that, numerical results on image restoration problems are given. It shows that our proposed algorithm is efficient and outperforms the other algorithms for this experiment.